Opposing and Operated Side Electroacupuncture Generates Similar Analgesic Effects on Pain after Knee Surgery. (23rd April 2021) - Huang, Hai; Song, Xiuling; Wang, Jiayou; Xing, Man; Kang, Bingxin; Ma, Chenghao; Li, Wenbiao; Han, Wenjun; Xiao, Lianbo; Chen, Yuelai
Abstract : The purpose of this study was to investigate whether opposing electroacupuncture (EA) could produce similar analgesic effects as operated side EA after knee surgery in rats. Sprague Dawley rats were randomly divided into the sham surgery group, and three surgery groups: opposing EA, operated side EA, and model. After surgery, compared with the sham surgery group, three kinds of pain behavior test methods (mechanical withdrawal threshold (MWT), cumulative pain score [CPS], and mechanical hypersensitivity of knee) were used to assess the pain behavior of the rats in the surgery groups. After knee surgery, the three surgery groups were intervened for three consecutive days: EA on the nonoperated side in the opposing EA group, EA on the operated side in the operated side EA group, and no intervention in the model group. It was shown that MWT was higher and CPS was lower in the two EA groups than in the model group on the first and second days after surgery. On the third day after surgery, MWT in the two EA groups was the highest among the 3 days, CPS was the lowest among the 3 days, and the number of nonvocalizations in rats also increased compared with the model group. Moreover, the MWT of the nonoperated side increased more in the opposing EA group than in the model and operated side EA groups. This indicated that both opposing EA and operated side EA methods can be used to relieve pain after knee joint surgery.